In Situ Studies of Phase Separation and Crystallization Directed by Marangoni Instabilities During Spin‐Coating. (7th October 2013) - Toolan, Daniel T. W.; Pullan, Nikki; Harvey, Michael J.; Topham, Paul D.; Howse, Jonathan R.
<x xml:space="preserve">Abstract</x> Results of a pioneering study are presented in which for the first time, crystallization, phase separation and Marangoni instabilities occurring during the spin‐coating of polymer blends are directly visualized, in real‐space and real‐time. The results provide exciting new insights into the process of self‐assembly, taking place during spin‐coating, paving the way for the rational design of processing conditions, to allow desired morphologies to be obtained. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>